Nonconvulsive Status Epilepticus Complicating Epstein-Barr Virus Encephalitis in a Child - Filippo Greco; Maria Donatella Cocuzza; Pierluigi Smilari; Giovanni Sorge; Lorenzo Pavone (Hindawi Limited, 2014)
Children with acute encephalopathy show prolonged electrographic seizure activity consistent with nonconvulsive status epilepticus (NCSE). Pediatric NCSE is a heterogeneous clinical entity with poor outcome and different etiologies, including central nervous system infection, stroke, toxic-metabolic syndrome, and epileptic syndrome. We report a 4-year-old girl with seizure and behavioral changes in whom the analysis of cerebrospinal fluid by polymerase chain reaction was positive for Epstein-Barr virus. We emphasize the importance of electroencephalography (EEG), and particularly, of continuous EEG monitoring for early recognition and appropriate treatment of this condition.